2017
DOI: 10.3390/su9101854
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact and Nutritional Improvement of Elevated CO2 Treatment: A Case Study of Spinach Production

Abstract: Abstract:The agriculture sector is known to be the one of the major contributors to global greenhouse gas (GHG) emissions. At the same time, global climate changes have affected the agriculture sector. In order to strengthen the sustainable development of agriculture, it is important to promote environmentally friendly farming and simultaneously increase the economic value. To improve the productivity of agriculture, technical advancements have occurred. Among those, we have focused on CO 2 treatment in cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…The main reason for the difference in impact scores is the direct emission of N 2 O greenhouse gas (GHGs) from the use of inorganic fertilizer in the integrated farming system. Seo et al [29], reported GWP values of 0.49 kgCO 2 eq./kg for integrated system and 0.29 kgCO 2 /kg spinach for eCO 2 system which are higher values obtained in this present study. Theurl et al [50] also reported similar range values of 0.094 and 0.115 kg CO 2 eq./kg fresh organic spinach under a polytunnel cultivation system, which is consistent with values obtained in this study.…”
Section: Global Warming (Gwp)contrasting
confidence: 71%
See 2 more Smart Citations
“…The main reason for the difference in impact scores is the direct emission of N 2 O greenhouse gas (GHGs) from the use of inorganic fertilizer in the integrated farming system. Seo et al [29], reported GWP values of 0.49 kgCO 2 eq./kg for integrated system and 0.29 kgCO 2 /kg spinach for eCO 2 system which are higher values obtained in this present study. Theurl et al [50] also reported similar range values of 0.094 and 0.115 kg CO 2 eq./kg fresh organic spinach under a polytunnel cultivation system, which is consistent with values obtained in this study.…”
Section: Global Warming (Gwp)contrasting
confidence: 71%
“…In Japan, Shiina et al [28] evaluated spinach production under a hybrid protective system where they reported its global warming potential (GWP) to be 2.3 kg CO 2 eq./kg spinach. In addition, Seo et al [29] reported 0.49 kgCO 2 eq. and 0.29 kgCO 2 /kg spinach for production under an integrated system and elevated CO 2 treatment production system, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agriculture sector is known to be one of the major contributors to global greenhouse gas (GHG) emissions. (Seo et al, 2017). As the livestock production index is interconnected with animal agriculture, it is vital to investigate this as well.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Along with numerous other studies, they also figured out that the agricultural sector was one of the highest contributors to the continuous changes in CO2 emissions in a certain country. (Seo et al, 2017)…”
Section: Country-specific Studies 231 Livestock Agriculturementioning
confidence: 99%